(untitled) (Scottish Historical and Archaeological Internet Reports, 2001)
The excavations produced a total assemblage of 372 sherds ranging in date from the 13th to the 20th century. Within this small assemblage there were 226 sherds dating from the 18th-, 19th- and 20th-century occupation of the site and these are not described in detail. The remaining 146 examples are described as a series of ceramic types per archaeological period. The typology is based largely on the major ceramic assemblage recovered by excavations in St Andrew’s, Fife.